Suppressing singlet–triplet annihilation processes to achieve highly efficient deep-blue AIE-based OLEDs. Issue 9 (5th July 2022) - Lin, Chengwei; Han, Pengbo; Qu, Fenlan; Xiao, Shu; Li, Yuanzhao; Xie, Dian; Qiao, Xianfeng; Yang, Dezhi; Dai, Yanfeng; Sun, Qian; Qin, Anjun; Tang, Ben Zhong; et al.
Abstract : The new concept of using a triplet–triplet annihilation (TTA) up-conversion material as a triplet scavenger to efficiently suppress singlet–triplet annihilation (STA), fabricating high-performance deep-blue AIE-based OLEDs. Abstract : Aggregation-induced emission (AIE) materials are attractive for the fabrication of high efficiency organic light-emitting diodes (OLEDs) by harnessing "hot excitons" from the high-lying triplet exciton states (T n, n ≥ 2) and high photoluminescence (PL) quantum efficiency in solid films. However, the electroluminescence (EL) efficiency of most AIE-based OLEDs does not meet our expectation due to some unrevealed exciton loss processes. Herein, we further enhance the efficiency of blue AIE-based OLEDs, and find experimentally and theoretically that the serious exciton loss is caused by the quenching of radiative singlet excitons and long-lived triplet excitons [singlet–triplet annihilation (STA)]. In order to suppress the STA process, 1-(2, 5-dimethyl-4-(1-pyrenyl)phenyl)pyrene (DMPPP) with triplet-triplet annihilation up-conversion was doped in two AIE emitters to reduce the triplet excitons on the lowest triplet excited state (T1 ) of AIE molecules. It can be seen that the external quantum efficiency (EQE) of the resulting blue OLEDs was enhanced to 11.8% with CIE coordinates of (0.15, 0.07) and a negligible efficiency roll-off, realizing the efficiency breakthrough of deep-blue AIE-based OLEDs. This work establishes a physical insight in revealing the exciton loss processes and the fabrication of high-performance AIE-based OLEDs.